Simplify −3/4r + 3 − 5/6r − 6.

1 answer

To simplify this expression, we need to combine like terms.

Combining the coefficients of the "r" terms, we have: (-3/4 - 5/6)r

To add these fractions, we need to find a common denominator. The least common multiple of 4 and 6 is 12.

Multiply the numerator and denominator of -3/4 by 3 to get -9/12.
Multiply the numerator and denominator of -5/6 by 2 to get -10/12.

So now we have: (-9/12 - 10/12)r

Simplifying the numerator gives us: -19/12r

And finally, combining the constant terms: 3 - 6 = -3

Therefore, the simplified expression is -19/12r - 3.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions